2019
DOI: 10.1111/1748-8583.12264
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of egalitarian pay: Reconceptualising its treatment in organisations

Abstract: In this paper, we offer an intraorganisational sensemaking perspective on how organisational members interpret egalitarian forms of pay. Specific focus is given to managerial (non)communication of diverse rationales for egalitarian pay practices. We integrate a wide range of research and descriptive accounts to organise schema‐relevant concepts into a typology of rationales that inform the sensemaking process, as ultimately observed in employee receptivity and response to egalitarian pay practices. The culmina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…However, the application of other allocation rules, such as equality and need, to distribute outcomes is also possible (see also Day et al., 2014; Fischer, 2016; Jany, 2021; Morand & Merriman, 2012; Olsen, 2015; Prince et al., 2020; Törnblom & Kazemi, 2011). Prior research suggests that, in collectivistic cultures, managers apply equality as the allocation rule to distribute outcomes equally among employees, independently of their inputs (Beugré, 2007; Kim & Gong, 2009; Leung, 2005; Morand et al., 2019; Olsen, 2015). If need is the allocation rule, managers distribute outcomes to those who have the greatest difficulties or needs of receiving the outcomes (Deutsch, 1985; Leung, 2005; Murphy‐Berman & Berman, 2002).…”
Section: Previous Research On Reward Allocation Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of other allocation rules, such as equality and need, to distribute outcomes is also possible (see also Day et al., 2014; Fischer, 2016; Jany, 2021; Morand & Merriman, 2012; Olsen, 2015; Prince et al., 2020; Törnblom & Kazemi, 2011). Prior research suggests that, in collectivistic cultures, managers apply equality as the allocation rule to distribute outcomes equally among employees, independently of their inputs (Beugré, 2007; Kim & Gong, 2009; Leung, 2005; Morand et al., 2019; Olsen, 2015). If need is the allocation rule, managers distribute outcomes to those who have the greatest difficulties or needs of receiving the outcomes (Deutsch, 1985; Leung, 2005; Murphy‐Berman & Berman, 2002).…”
Section: Previous Research On Reward Allocation Rulesmentioning
confidence: 99%
“…This task is particularly challenging for multinational organisations because employees in today's globalised business world often have different cultural backgrounds and therefore different expectations about reward allocations (Frank et al., 2015; Načinović Braje et al., 2019; Olsen, 2015; Prince et al., 2020; Scott et al., 2015). Employee compensation is an important motivation tool (Caza et al., 2015; Gahan et al., 2021; Hewett & Leroy, 2019; Morand et al., 2019; Park & Kruse, 2013; Parker et al., 2019) and at the same time the largest operation cost for many organisations (Gerhart et al., 2009). To design effective reward systems, managers and organisations need to better understand their employees' preferences for reward allocation rules.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that workplace bullying takes the form of unmanageable workload, lack of respect for opinions and views, and sensual assault (Bentley, 2015)., which can cause psychological and work-related stress (Rai & Agarwal, 2018). When workers build social exchange relationships between organizations, they appear to perform well and demonstrate successful work attitudes and behaviors (Hendricks et al, 2018) with integrity as a balance (Morand, Merriman, & Deckop, 2020). Theoretical studies have examined workplace bullying, including emotional abuse, harassment, victimization, and antagonism (Akella & Seay, 2022).…”
Section: Introductionmentioning
confidence: 99%